DISPARITAS SOSIOKULTURAL LEMBAGA TUHA PEUT DAN BADAN PERMUSYAWARATAN DESA DALAM KONSEPSI NEGARA KESATUAN - Sani, Abdullah; Al-Qardhawy, M. Yusuf (Jurnal Sosial Humaniora Sigli, 2024)
This research aims to identify the authorities possessed by Tuha Peut and the Village Consultative Body (BPD) as well as the disparities between the two in the concept of a unitary state. This research uses a qualitative method in the form of legal norms as a legal basis which is normative juridical in nature. There are three main things that are the focus of this research, first regarding the authority possessed by Tuha Peut in Aceh as mandated in Aceh Qanun Number 10 of 2008 concerning Traditional Institutions, second regarding the authority possessed by BPD as regulated in Law Number 6 of 2014 regarding Villages and other legal norms, and third regarding the quite significant disparity between Tuha Peut and BPD. The research results show that: first, there are several disparities in authority and treatment between the Tuha Peut institution in Aceh and the BPD in other provinces in Indonesia. Some of the disparities that are quite significant include Tuha Peut being found in the gampong and at the residential level, while the BPD is only found at the gampong level. Another disparity regarding term of service, Tuha Peut is only 6 years, while BPD is 8 years. Tuha Peut does not get post-service benefits, while BPD does. Another thing is that the BPD does not have the authority to impose sanctions to remove perpetrators of violations of customs and customary law from the gampong, while Tuha Peut does.Keywords : Authority, Tuha Peuet, Village Consultative Body, Disparity, and, Sociocultural